Kategorisasi PNS dan PPPK dalam Undang-Undang Nomor 5 Tahun 2014 tentang ASN ditinjau dari Sudut Pandang Transisi Kepegawaian - Indra Budi Sumantoro (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2018)
The regulation regarding civil servants is generally not different from the previous regulation as it is stipulated in the Act on The Principles of The Employee Affair with its regulations, implementations, and improvements of the Human Resource Management aspects i.e., recruitments and selections, career trainings and developments, placements of positions, performance appraisals, discipline and neutrality, salary and benefits, social security, until terminations. However, this is not stipulated in Government Employees and Work Agreement. In addition, The Draft of Government Regulation on Government Employees and Work Agreement Management has not been formally ratified and published into Government Regulation. The discussion in preparing a draft of the Act on the State Civil Apparatus raised the issues on the non-civil servant professionals whose their expertise was needed but they could not be recruited as a civil servant due to the personnel administration requirements, particularly on ages that were more than 35 years old. The purpose of establishing Government Employees and Work Agreement is to recruit the best citizens who are administratively not considered as the civil servant seen on ages. The categorization of Government Employees and Work Agreement and Civil Servants does not have an obvious concept so that it is necessary to revise the Act on State Civil Apparatus by considering the personnel transition method.Keywords - Government Employees and Work Agreement, Employee Affair, Recruitment